Determination of Constructs and Dimensions of Employability Skills Based Work Performance Prediction: A Triangular Approach - Rahmat, Normala; Buntat, Yahya; Ayub, Abdul Rahman (International Journal of Economics and Financial Issues, 2015)
The level of the employability skills of the graduates as determined by job role and mapped to the employability skills, which correspond to the requirement of employers, will have significant impact on the graduates' job performance. The main objective of this study was to identify the constructs and dimensions of employability skills, which can predict the work performance of electronic polytechnic graduate in electrical and electronics industry. A triangular qualitative approach was used in the early stages in the development of research constructs and dimensions employability skills based work performance prediction (ESWPP) of document analysis and expert interview protocol from the electrical and electronics industry and the institutions perspective. Document analysis was done by using frequency matrices tables while interview data involving experts from industry and institution were analyzed using Fleiss Kappa reliability. Fleiss Kappa reliability analysis is used to determine the overall dimensions of the approval index for each construct ESWPP. The findings of the overall Kappa coefficient value at 0.91 and 0.99 for the industry and the academia, which indicates the level of agreement, is very good. The results showed that the constructs and dimensions ESWPP were communication skills, personal qualities, teamwork skills, critical thinking skills and problem solving, technology skills, organizational skills and learning skills. Keywords: Employability Skills; Graduate Electronic Polytechnic; Job Roles; Construct, Dimensions JEL Classifications: M001